A bibliometric evaluation of postgraduate thesis on internet of things (IoT) in Turkey - Özcüre, Osman Güray; Tonkal, Özgür (İdris Karagöz, 2026)
In this study, 706 postgraduate theses (master’s and doctoral) accessible in the Council of Higher Education Thesis Center (YÖK Ulusal Tez Merkezi) as of May 20, 2025, in the field of IoT were evaluated bibliometrically. The theses cover 2015–2024; 2025 was excluded as the year had not been completed at the time of the study. The aim was to reveal academic trends in IoT research in Turkey and provide guiding insights for researchers. Bibliometric analysis was divided into institutional and content analyses. While the institutional analysis covers all theses, the content analysis focuses on 375 theses published between 2022 and 2024 to identify recent trends. Excel functions, the WordCounter (wordcounter.ai) web tool and Python codes developed within the context of content analysis for generating a unique Turkish index list and heatmap were used. The scripts are included in the Appendix. Findings show Altınbaş University leads with 90 theses, most conducted in Computer Engineering (206) and Electrical-Electronics Engineering (100). Thesis production fell during the pandemic but peaked in 2022 with 173 theses. Machine Learning, Deep Learning, and Cybersecurity emerged as leading thematic areas, while Industry 4.0, Blockchain, and Embedded Systems remain underexplored. The heatmap revealed co-occurrence patterns among thematic areas, while the trend forecast indicated a potential rise in research on Cybersecurity, Machine Learning and Internet of Things. This study stands out for its 2015–2024 coverage, methodology, and in-depth analysis, serving as a comprehensive reference on IoT research trends in Turkey.
Keywords: Cyberphysical Systems and Internet of Things; Siberfizik Sistemleri ve Nesnelerin İnterneti [EN] Data Analysis; Veri Analizi